The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf01447209
|View full text |Cite
|
Sign up to set email alerts
|

Social problem solving: A moderator of the relation between negative life stress and depression symptoms in children

Abstract: The social problem-solving skill of generating effective alternative solutions was tested as a moderator of the relation between negative life stress and depressed mood in children. Boys (n = 25) and girls (n = 25), ages 8 to 12 years, from inner-city, lower socioeconomic group families, completed measures of depression symptoms, negative impact of life events, and quantity and effectiveness of alternative solutions to social problems. Results indicated that the effectiveness of alternative solutions children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 32 publications
6
48
0
Order By: Relevance
“…In contrast, this pattern was not observed for social anxiety. This supports previous findings that depression is associated with lower skills in problemsolving (see Goodman et al 1995;Sacco and Graves 1984), although the moderating effect of peer acceptance suggests that having at least some positive social relations to draw upon could facilitate the use of problem-solving strategies. As outlined earlier, conceptual and empirical work on specificity of thought in anxiety and depression suggests that the cognition of children higher in depressive symptoms is rooted in a greater sense of hopelessness and degradation (see Kendall and Ingram 1989), rendering them less likely to adopt proactive coping strategies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, this pattern was not observed for social anxiety. This supports previous findings that depression is associated with lower skills in problemsolving (see Goodman et al 1995;Sacco and Graves 1984), although the moderating effect of peer acceptance suggests that having at least some positive social relations to draw upon could facilitate the use of problem-solving strategies. As outlined earlier, conceptual and empirical work on specificity of thought in anxiety and depression suggests that the cognition of children higher in depressive symptoms is rooted in a greater sense of hopelessness and degradation (see Kendall and Ingram 1989), rendering them less likely to adopt proactive coping strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Both of these strategies are likely to be inhibited by enduring negative self-schemas which create a sense of hopelessness (related to the combination of high negative affect and low positive affect, as described in the tripartite model). Thus, even though problem-solving strategies have generally been negatively associated with internalising symptoms (e.g., Kochendefer-Ladd 2004), difficulties in orienting to a problem in order to find solutions are especially likely to be associated with depressive symptoms (see Goodman et al 1995;Ogul and Gencoz 2003;Sacco and Graves 1984). In contrast, as Daleiden and Vasey (1997, p. 418) conclude from their review of research on information-processing characteristics, "there is a clear indication that many responses accessed by anxious children … are proactive and problem-focused in nature", possibly reflecting the active intention to ward off perceived threats and reduce the core symptom of arousal.…”
Section: The Relationship Between Coping Strategies and Depression Anmentioning
confidence: 99%
“…A number of studies have shown that social problem solving ability, either by itself, or together with social support, can reduce or minimize the impact of life stress on individuals (Dubow & Tisak, 1989;Dubow, Tisak, Causey, & Hryshko, 1991;D'Zurilla & Sheedy, 1991;Goodman, Gravitt, & Kaslow, 1995). Social problem solving abilities are found to moderate the relationship between negative life stress and measures of distress such as hopelessness (Bonner & Rich, 1988), anxiety (Nezu, 1986a), depressive symptoms (Nezu, 1986b), and behavioral and academic adjustment (Kang & Lee, 1992).…”
mentioning
confidence: 99%
“…Toward this end, these data reveal a small subset of common skills that may offer community providers the biggest bang for their buck in prevention programming, beginning with problem solving. Although it was beyond the scope of the present study to examine directly the associations of specific common elements with positive youth outcomes, a rich and extensive literature provides support for problem solving as an effective tool for promoting healthy trajectories (Dubow and Tisak 1989;Dubow, Tisak, ,Causey & Hryshko, 1991;D'Zurilla and Sheedy, 1991;Goodman, Gravitt, & Kaslow, 1995 Reinecke, Dattilio, & Freeman, 2006;FIG-TESPM, Elias & Tobias, 1990), corresponding perhaps to the wide range of life problems for which it can be applied, including interpersonal conflict, sexual risk-taking, exposure to alcohol and drugs, and problems of daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we addressed the unique needs of YFC as previously described and outlined in Figure 1: (1) Access to condoms: Youth received a supply of condoms before leaving the shelter and information about where to access free condoms in their community; (2) Ambivalence towards teen pregnancy: Ambivalence was addressed explicitly through a role playing activity in which youth described the disadvantages of teen parenting to a "friend" who wanted to get pregnant; (3) Broader vulnerability: We added a problem-solving module, reflecting findings that problem-solving is ubiquitous to mental health intervention and prevention programs (eg: Goodman, Gravitt, & Kaslow, 1995), to strengthen resilience and reduce risk for co-occurring conduct problems (e.g., substance use, delinquency). The resulting adapted intervention was named SiHLE-YFC: Smart teens Informing, Healing, Living, Empowering for Youth in Foster Care.…”
Section: Methodsmentioning
confidence: 99%